2017
DOI: 10.1007/s10916-017-0734-3
|View full text |Cite
|
Sign up to set email alerts
|

Level of Digitization in Dutch Hospitals and the Lengths of Stay of Patients with Colorectal Cancer

Abstract: A substantial amount of research has been published on the association between the use of electronic medical records (EMRs) and quality outcomes in U.S. hospitals, while limited research has focused on the Western European experience. The purpose of this study is to explore the association between the use of EMR technologies in Dutch hospitals and length of stay after colorectal cancer surgery. Two data sets were leveraged for this study; the HIMSS Analytics Electronic Medical Record Adoption Model (EMRAMSM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Prior research has shown that clinical decision support systems like ANNs may be connected and embedded with EMR systems [89]. Because of the documented improvements in clinical decision making when clinicians utilize EMR systems [90], integrating the ANN transfusion prediction decision support system with an EMR or surgical planning system would facilitate access by integrating the ANN transfusion prediction decision support tool into their workflow, which would further improve blood bank planning and surgical and post-operative preparation [91] and consequently improve patient outcomes. The ANN would be able to alert surgeons to possible unexpected complications that would lead to a transfusion even if none were anticipated and could also be used to confirm the necessity of surgeon blood orders.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that clinical decision support systems like ANNs may be connected and embedded with EMR systems [89]. Because of the documented improvements in clinical decision making when clinicians utilize EMR systems [90], integrating the ANN transfusion prediction decision support system with an EMR or surgical planning system would facilitate access by integrating the ANN transfusion prediction decision support tool into their workflow, which would further improve blood bank planning and surgical and post-operative preparation [91] and consequently improve patient outcomes. The ANN would be able to alert surgeons to possible unexpected complications that would lead to a transfusion even if none were anticipated and could also be used to confirm the necessity of surgeon blood orders.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between response rates and outcomes could be informative, for example, when response rates are considered a proxy for certain structures or processes of care organization that may influence the outcome (assuming adequate adjustment for case mix). For example, digitization in hospitals can ease recruitment and may also improve outcomes 21 …”
Section: Interpretation Of Funnel Plotsmentioning
confidence: 99%
“…For example, digitization in hospitals can ease recruitment and may also improve outcomes. 21 Hospital comparison research usually aims to explore whether there is an association between the treating hospital and the patients' outcome. Herein, factors that affect both the outcome and the hospital in which the patient is treated should be taken into account, that is, confounding factors ( Figure B2).…”
Section: Relationship With Volumementioning
confidence: 99%
“…Nevertheless, informed patient consent and patient anamnesis obtained during patient-physician interactions are still mainly archived in hard-copy form and remain unavailable for further use. Digitization has the potential to increase the efficiency of healthcare systems [1]: improved software technology and mobile devices, meanwhile, can help to spread this technology into hospitals [2][3][4][5]. Particularly in radiology departments, high levels of digitization are already common and necessary; however, PA and patients' current clinical problems are often incomplete, outdated, or inaccessible [6].…”
Section: Introductionmentioning
confidence: 99%